2022
DOI: 10.3389/fnagi.2021.787654
|View full text |Cite
|
Sign up to set email alerts
|

Aging-Related Changes in Cortical Sources of Sleep Oscillatory Neural Activity Following Motor Learning Reflect Contributions of Cortical Thickness and Pre-sleep Functional Activity

Abstract: Oscillatory neural activity during sleep, such as that in the delta and sigma bands, is important for motor learning consolidation. This activity is reduced with typical aging, and this reduction may contribute to aging-related declines in motor learning consolidation. Evidence suggests that brain regions involved in motor learning contribute to oscillatory neural activity during subsequent sleep. However, aging-related differences in regional contributions to sleep oscillatory activity following motor learnin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 133 publications
0
1
0
Order By: Relevance
“…The SMA is closely related to motor control and execution, and there is a strong association between movement and sleep ( Gong et al, 2020 ; Fitzroy et al, 2022 ). Studies have shown that exercise can improve sleep quality, while lack of exercise may lead to sleep problems ( Santarnecchi et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…The SMA is closely related to motor control and execution, and there is a strong association between movement and sleep ( Gong et al, 2020 ; Fitzroy et al, 2022 ). Studies have shown that exercise can improve sleep quality, while lack of exercise may lead to sleep problems ( Santarnecchi et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%